Entrance gateway of the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Pictured here is the north-facing view of the two-storeyed entrance gateway of the Mahanaleshwar temple complex. It is a semi-open space with a porch on the ground floor, a plain balcony with dwarf walls on the first floor, and a canopy with a pyramidical spire on the top.